2018
DOI: 10.3892/mmr.2018.8523
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑195 is associated with regulating the pathophysiologic process of human laryngeal squamous cell carcinoma

Abstract: MicroRNAs (miRNAs) have been reported to be associated with the modulation of tumor development, including alterations associated with the development of human laryngeal squamous cell carcinoma (LSCC). The present study was designed to investigate whether miRNA‑195 was associated with the pathophysiologic process of human LSCC and to identify its potential roles and underlying molecular mechanisms. To determine whether miRNA‑195 serves a role in LSCC, reverse transcription‑quantitative polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Subsequently, CCK-8, wound healing and Transwell assays, and western blot analysis, were used to examine the effects of miR-195-5p overexpression on the proliferation, migration and invasion of laryngeal cancer cells. Pang et al ( 21 ) reported that miR-195 is associated with the cell viability of the AMC-HN-8 cell line. In the present study, the results of CCK-8 assay revealed that miR-195-5p overexpression significantly inhibited the proliferation of AMC-HN-8 cells compared with the control group ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, CCK-8, wound healing and Transwell assays, and western blot analysis, were used to examine the effects of miR-195-5p overexpression on the proliferation, migration and invasion of laryngeal cancer cells. Pang et al ( 21 ) reported that miR-195 is associated with the cell viability of the AMC-HN-8 cell line. In the present study, the results of CCK-8 assay revealed that miR-195-5p overexpression significantly inhibited the proliferation of AMC-HN-8 cells compared with the control group ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, miR-195-5p overexpression has been shown to suppress the proliferation of lung cancer cells, and to induce apoptosis and G 0 /G 1 phase arrest ( 30 ). Importantly, miR-195 is reported to be associated with regulating the pathophysiologic process of human laryngeal squamous cell carcinoma ( 21 ). In the present study, the expression of miR-195-5p in laryngeal cancer cells was found to be significantly lower compared with that in normal cells, which was consistent with the expression of miR-195-5p in other types of tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed to detect the protein expression levels of CDC42 and CCND1 from tissues and cells, as previously described ( 13 ). Total proteins were extracted with RIPA buffer (Beyotime Institute of Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…For example, miR-195 has been observed to be downregulated in EOC, and was revealed to decrease cell proliferation and induce apoptosis of human OVCAR-3 cells by inhibiting VEGFR2 and AKT signaling ( 12 ). In addition, miR-195 is downregulated in human laryngeal squamous cell carcinoma, while the overexpression of miR-195 inhibits cell viability, migration and invasion, as well as promotes apoptosis of AMC-HN-8 cells ( 13 ). However, the roles of miR-195 in the cell cycle, migration and invasion of EOC cells are yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…According to reports, miRNAs are significant in gene expression, regulation, and cell signaling transduction [8]. MiRNAs engage in multiple steps which are critical for cancer progression, including cell survival, proliferation, specialization, migration, and apoptosis [9][10][11]. Further, miRNAs have been linked with the tumorigenesis of OSCC.…”
Section: Introductionmentioning
confidence: 99%